Knowledge and practice of preventive behaviour regarding kidney stone disease recurrence among patients in Hospital Pakar Universiti Sains Malaysia - Nazir, Muhammad Nurhamka Mohd (Universiti Sains Malaysia, 2025)
Kidney stone disease (KSD) is a recurrent condition that can lead to significant health problems and costs. Preventive behaviours, such as drinking enough water, dietary changes, and medical follow-up, are essential to reduce recurrence. This study aimed to determine the level of knowledge and practice of preventive behaviour among patients at Hospital Pakar Universiti Sains Malaysia (HPUSM). A total of 60 patients completed a self-administered questionnaire. Data were analysed using descriptive statistics and inferential tests with SPSS version 26.0. The mean knowledge score was 1.57 (SD = 0.50), with 56.7% of participants showing good knowledge. The mean practice score was 2.25 (SD = 0.628), with 55.0% showing moderate practice. Pearson’s correlation showed a weak and non-significant relationship between knowledge and practice (r = 0.132, p = 0.315). However, education level was significantly associated with both knowledge (p < 0.001) and practice (p = 0.005), while age and gender were not. In conclusion, while patients had moderate to good knowledge and practice, there was a gap in translating knowledge into consistent practice. Targeted education and support are needed to improve preventive behaviours and reduce KSD recurrence